PARASITOLOGICALASSESSMENT AND HOST-PARASITE RELATIONSHIP IN FARMED CACHARA CATFISH FINGERLINGS (PSEUDOPLATYSTOMA RETICULATUM EIGENMANN & EIGENMANN 1889), MATO GROSSO DO SUL, BRAZIL - Benites de Pádua, Santiago (2014)
Farmed fingerlings of South American catfish are frequently exposed to several parasites, but little information is available for implementing health programs for control and prevention of parasitic diseases in the hatcheries. This study evaluated the parasitic fauna of cachara catfish fingerlings (Pseudoplatystoma reticulatum Eingenmann & Eigenmann, 1889) and the hostparasite relationship during the early stages of rearing. A total of 302 cachara fingerlings were used for parasitic diagnosis and histopathological analysis. Ichthyophthirius multifiliis and Trichodina heterodentata were diagnosed as the most prevalent parasites, followed by Cryptobia sp., Henneguya sp., Monogenea and Nematoda. There was a positive correlation between the size of the fish and the mean intensity of parasitism by I. multifiliis. Proliferation of mucus cells, club cells, multifocal area of degeneration, epithelial necrosis on the body surface, skin ulceration, fusion of secondary gill lamellae and inflammatory infiltration were observed in I. multifiliisinfected fish. Ciliated protozoans were the main etiological agents diagnosed, and the cachara (P. reticulatum) is a new host for T. heterodentata. In addition, ichthyophthiriasis induced severe tissue damage thus making the fingerlings susceptible to opportunistic infections.